STUDI EFEKTIVITAS LEAFLET TERHADAP SKOR PENGETAHUAN REMAJA PUTRI TENTANG DISMENOREA DI SMP KRISTEN 01 PURWOKERTO KABUPATEN BANYUMAS - Kawurian, Raras; Fajarsari, Dyah; Mulidah, Siti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Many girls feel pain when menstruation comes. This complaint called dismenorrhea and usually occurs 2 or 3 years after menarche. Girlâ€™s knowledge about dismenorrhea is far from what people expected, there must be information media to increase their knowledge. One of the information media which can be used beside tv, radio, poster, brochure, magazine, and newspaper is leaflet. To find out the effectiveness of leaflet toward girls knowledge score about dismenorrhea. The research population was female teenager of Christian Junior High School 01 of Purwokerto years of 2010. The sample was 50 persons. The data was analyzed was using average score of knowledge level and pair â€œtâ€ test. 1) the girls knowledge average score before accepting the leaflet is 55,20, this result shows the less of their knowledge. 2) The girls knowledge average score after accepting the leaflet is increasing become 74,00, this result shows the better knowledge. 3) The leaflet effectiveness toward the change of girls knowledge about dismenorrhea, (P=0,000). Leaflet is very effective toward the change of girls knowledge about dismenorrhea. Â  Key words: Leaflet, knowledge score.